Lower limb sports compression garments improve muscle blood flow and exercise performance during repeated-sprint cycling - Broatch, J. R.; Bishop, D. J.; Halson, S. (International Journal of Sports Physiology and Performance, 2018)
Purpose: Evidence supporting the use of lower-limb compression garments during repeated-sprint exercise (RSE) with short rest periods, where performance will rely heavily on aerobic metabolism, is lacking. Methods: A total of 20 recreationally active participants completed 2 cycling RSE sessions, with and without lower-limb compression tights. The RSE session consisted of 4 sets of 10?×?6-s maximal sprints on a wind-braked cycle ergometer, interspaced by 24 s of recovery between bouts and 2 min of recovery between sets. Muscle oxygen consumption (mV.O2) of, and blood flow (mBF) to, the right vastus lateralis muscle was measured during exercise using near-infrared spectroscopy and venous/arterial occlusions of the right lower limb. Cycling performance, oxygen consumption (mV.O2), heart rate, and capillary blood samples (lactate, pH, bicarbonate, and base excess) were also measured/taken throughout the session. Results: Compared with control, peak power (40.7 [19.9] W; mean?±?95% confidence intervals) and mBF (0.101 [0.061] mL·min-1·100 g-1) were higher, and heart rate (2 [1] beats/min) was lower, when participants wore compression (P<.05). mV.O2 VO2, blood lactate, and heart rate increased as a result of exercise (P<.05), with no differences between conditions. Similarly, blood pH, bicarbonate, and base excess decreased as a result of exercise (P<.05), with no difference between conditions. Conclusions: Wearing lower-limb compression tights during RSE with short intervals of rest improved cycling performance, vastus lateralis mBF, and heart rate. These results provide novel data to support the notion that lower-limb compression garments aid RSE performance, which may be related to local and/or central blood flow.